Rodrigo Duterte and the populist backlash against globalization - Heydarian, Richard Javad (Animo Repository, 2017)
The article discusses the impact of populism in the globalization. Topics discusses include diffusion of technology, capital, and free market values across the developing world; challenges of corruption, overpopulation, inequality in the Philippines; and contribution of Rodrigo Duterte, President of the Philippines in globalization.